Funkcije ponavljanj v govorjenem narečnem diskurzu - Zuljan Kumar, Danila (Slavistična revija, 2007)
In spoken language reiterations have a significant role. In addition to establishing and maintaining the coherence, i.e., as repeated or partially repeated occurences, they have many other functions, of which the speakers are more or less aware. The article focuses on various types of reiternations and their functions in the extemporaneous dialectal speech. The texts were recorded in Brda.
Keywords: coherence; dialectal speech; koherenca; narečni govor; ponavljanja; reiterations; Slovene language; slovenščina; spontani narečni govor